Influence of a dosing-time on toxicities induced by docetaxel, cisplatin and 5-fluorouracil in patients with oral squamous cell carcinoma; a cross-over pilot study. (1st February 2018) - Tsuchiya, Yoshiyuki; Ushijima, Kentaro; Noguchi, Tadahide; Okada, Naruo; Hayasaka, Jun-ichi; Jinbu, Yoshinori; Ando, Hitoshi; Mori, Yoshiyuki; Kusama, Mikio; Fujimura, Akio
ABSTRACT: Docetaxel, cisplatin plus fluorouracil (DCF) regimen is a useful chemotherapy, but is sometimes withdrawn due to severe adverse effects (AE). In this study, we examined whether the chronotherapy of DCF regimen could reduce the drugs-induced toxicities in clinical practice. Patients with oral squamous cell carcinoma were enrolled. Chemotherapy started at 10:30 (Morning-dosing) or 18:30 (Evening-dosing) for 5 days by a cross-over design. AE were assessed for 14 days after an initiation of each dosing. The grades of nausea, vomiting and neutropenia were smaller during Evening-dosing than during Morning-dosing. These data suggest that the chrono-chemotherapy might provide a merit for reducing the DCF regimen-related severe AE.